Towards an understanding of the success factors in international twinning and sister-city relationships - J. C. De Villiers; T. J. De Coning; E. V.D.M. Smit (South African Journal of Business Management, 2007)
The twinning of cities has evolved from an international instrument of friendship and cultural exchange to a powerful tool for capacity building and economic development. Within this context it can be defined as a `long-term strategic alliance between communities in different cities or towns, in which their municipalities are key actors'. There exists, however, a paucity of research about the twinning phenomenon and its success factors. In order to understand more fully which factors contribute to success, success factors reported in the available literature were identified, and a number of hypotheses formulated. These were then empirically tested from a survey conducted amongst all the municipalities of South Africa.
Keywords: 650